Behaviour of retrofitted masonry walls subjected to blast loading: Damage assessment. (15th December 2019) - Chiquito, M.; López, L.M.; Castedo, R.; Pérez-Caldentey, A.; Santos, A.P.
Highlights: Three protective solutions have been tested on brick masonry walls against blast. Results have been analyzed to make a damage assessment and establish damage levels. The better solution studied is the glass fibre, followed by the carbon fibre. Panels with the fibre reinforced mortar retrofitting do not show good results. The reinforcement is more effective when placed on the inner face of the wall. Abstract: The response of brick masonry walls against blast loads has become an important topic in recent years. The debris from masonry walls or their collapse can become a major hazard when the main structure does not collapse. In this paper, a damage assessment of brick masonry walls subjected to blast loading is presented. For this purpose, three different retrofitting solutions have been tested in four full-scale experimental tests and compared with a control non-reinforced brick panel. The protective solutions which have been considered can be applied in a simple way, both in new or existing buildings. For the evaluation, several parameters have been collected and analyzed combining visual observations and analytical methods. Damage levels range from moderate damage to collapse. Among the three types of retrofitting solutions tested, results show that two of them were effective for strengthening brick masonry wall panels against blast loading.